Księdza Józefa Kentenicha koncepcja praktycznej wiary w Opatrzność Bożą - Skąpski , Przemysław (Łódzkie Studia Teologiczne, 2025)
Practical faith in Divine Providence is an original concept in the theology and spirituality of the Schoenstatt Movement, whose founder is Joseph Kentenich. This is the practical application of the dogmatic truth about God’s Providence in life. It involves, first of all, trying to read God’s will in the world using three specific sources of recognition: being, time and the soul. Secondly, it is about actively responding to the truth we have identified by responsibly shaping our lives. In this context, Kentenich formulated two principles: „open door” and „creative result”, in order to improve and make the discernment of God’s will more reliable.